Possible Implications of Managing Alexithymia on Quality of Life in Parkinson’s Disease: A Systematic Review - Laura Culicetto; Caterina Formica; Viviana Lo Buono; Desirèe Latella; Giuseppa Maresca; Amelia Brigandì; Chiara Sorbera; Giuseppe Di Lorenzo; Angelo Quartarone; Silvia Marino (Parkinson's Disease, 2024)
Alexithymia, characterized by difficulty in recognizing and verbalizing emotions, is reported to be more prevalent in subjects with Parkinson’s disease (PD) than in the general population. Although it is one of the nonmotor symptoms of PD, alexithymia is often overlooked in clinical practice. The aim of this systematic review is to investigate the prevalence of alexithymia in PD, assess its impact on quality of life, and explore the rehabilitation approaches for alexithymia. Research articles, selected from PubMed, Scopus, and Web of Science, were limited to those published in English from 2013 to 2023. The search terms combined were “Alexithymia,” “Parkinson’s disease,”, and “Quality of life.” Current literature review indicates that alexithymia is commonly assessed using the Toronto Alexithymia Scale (TAS-20), and it is associated with deficits in visuospatial and executive functions. Presently, rehabilitation interventions for alexithymia are scarce, and their effectiveness remains controversial. Future research should focus on developing comprehensive assessments and rehabilitation strategies for emotional processing, considering its significant impact on the quality of life of both patients and caregivers.